The Role of Nitric Oxide in the Dysregulation of the Urine Concentration Mechanism in Diabetes Mellitus - Cipriani, Penelope; Kim, Sunhye L.; Klein, Janet D.; Sim, Jae H.; von Bergen, Tobias N.; Blount, Mitsi A. (Frontiers in Physiology, 2012)
Uncontrolled diabetes mellitus results in osmotic diuresis. Diabetic patients have lowered nitric oxide (NO) which may exacerbate polyuria. We examined how lack of NO affects the transporters involved in urine concentration in diabetic animals. Diabetes was induced in rats by streptozotocin. Control and diabetic rats were given L-NAME for 3 weeks. Urine osmolality, urine output, and expression of urea and water transporters and the Na-K-2Cl cotransporter were examined. Predictably, diabetic rats presented with polyuria (increased urine volume and decreased urine osmolality). Although metabolic parameters of control rats were unaffected by L-NAME, treated diabetic rats produced 30% less urine and osmolality was restored. UT-A1 and UT-A3 were significantly increased in diabetic-rat inner medulla. While L-NAME treatment alone did not alter UT-A1 or UT-A3 abundance, absence of NO prevented the upregulation of both transporters in diabetic rats. Similarly, AQP2 and NKCC2 abundance was increased in diabetic animals however, expression of these transporters were unchanged by L-NAME treatment of diabetes. Increased expression of the concentrating transporters observed in diabetic rats provides a compensatory mechanism to decrease solute loss despite persistent glycosuria. Our studies found that although diabetic-induced glycosylation remained increased, total protein expression was decreased to control levels in diabetic rats treated with L-NAME. While the role of NO in urine concentration remains unclear, lowered NO associated with diabetes may be deleterious to the transporters’ response to the subsequent osmotic diuresis.